2010
DOI: 10.1186/1465-9921-11-31
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 protects against pulmonary fibrosis by regulating the lung oxidant level and Th1/Th2 balance

Abstract: BackgroundPulmonary fibrosis is a progressive and lethal disorder. Although the precise mechanisms of pulmonary fibrosis are not fully understood, oxidant/antioxidant and Th1/Th2 balances may play an important role in many of the processes of inflammation and fibrosis. The transcription factor Nrf2 acts as a critical regulator for various inflammatory and immune responses by controlling oxidative stress. We therefore investigated the protective role of Nrf2 against the development of pulmonary fibrosis.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(122 citation statements)
references
References 46 publications
6
110
3
Order By: Relevance
“…The role of Nrf2 as a critical mediator of the antioxidant response has been well studied. Previous studies demonstrate that Nrf2 deficiency exacerbates inflammation and oxidative stress in a variety of disease models, including emphysema (38), COPD exacerbations (13), acute lung injury (31,42), pulmonary fibrosis (6,22), and sepsis (53). Alternatively, activation of Nrf2 in these disease models reduces oxidative stress and inflammation (24,43,49).…”
Section: Discussionmentioning
confidence: 99%
“…The role of Nrf2 as a critical mediator of the antioxidant response has been well studied. Previous studies demonstrate that Nrf2 deficiency exacerbates inflammation and oxidative stress in a variety of disease models, including emphysema (38), COPD exacerbations (13), acute lung injury (31,42), pulmonary fibrosis (6,22), and sepsis (53). Alternatively, activation of Nrf2 in these disease models reduces oxidative stress and inflammation (24,43,49).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with severe chronic obstructive pulmonary disease, there were increased Gal-3 expression and neutrophil accumulation in the small airway epithelium, along with epithelial proliferation and airway obstruction (Pilette et al, 2007). Other research demonstrated that Gal-3 knockdown mice developed a lower Th2 response but a higher Th1 response, which played a significant role in the processes of inflammation and fibrosis (Zuberi et al, 2004;Kikuchi et al, 2010).…”
Section: Functions Of Gal-3mentioning
confidence: 99%
“…The chemotherapeutic agent, BLM, has been demonstrated to cause oxidative lung injuries in mice, and BLM-treated mice are considered to be a classical model of idiopathic pulmonary fibrosis (25). Currently, only a few genes involved in the control of ROS have been implicated in the pathogenesis of pulmonary fibrosis in mouse knockout models (18), including Nrf2 as a sole transcription factor among these genes (12). Furthermore, Nrf2 was activated and its targets, including Nqo1, were upregulated in mice treated with BLM (23).…”
Section: Discussionmentioning
confidence: 99%
“…Klf9 is a ubiquitously expressed member of the Sp1 C2H2-type zinc finger family of transcription factors (12). The expression of Klf9 can be increased by several stress-inducing agents, including the proteasomal inhibitor, bortezomib, and the histone deacetylase inhibitor, panobinostat, and Klf9 in turn mediates their cytotoxicity (13).…”
Section: Introductionmentioning
confidence: 99%